The Impact of a Social-Constructivism Instructional Program on Eleventh-grade Female Students’ English Reading and Writing Skills in Jordan - Alkhawaldeh, Fatima Abdalaziz; Al-Omari, Hamzah Ali (Dirasat: Human and Social Sciences, 2025)
Objectives: This study investigates the effectiveness of an instructional program based on social constructivism in improving English language reading skills among eleventh-grade female students in Jordan. Methods: A quasi-experimental study approach was adopted during the first semester of the scholastic year 2023-2024 at Alqweismeh School for Girls at Alqweismeh Directorate. The study sample consisted of 46 students in two sections, randomly distributed to a control group (25 students), and an experimental group (21 students). Reading tests were used to assess the reading skills of both groups. The study data was collected using a single research tool: a comprehensive English achievement pre-and-post reading test, based on a verbal rating scale. The data was analyzed using mean averages, standard deviations, and ANCOVA. Results: The study findings indicate a statistically significant difference (α=0.05) between the mean scores of either group (experimental or control) regarding their English language reading skills. The mean score of the experimental group was (14.86 + 3.72) compared to the mean score of the control group (10.00 + 3.27). The reading achievement was in favor of the experimental group. Conclusions: The study findings indicate that the instructional program, based on social constructivism, is significantly more effective than the conventional method in developing students’ English language reading skills. The study recommends that English language reading skills be improved by including social constructivism tenets in English language curricula and instruction methods.